Fortifying Data Security: Node.js Authentication, Authorization, and the Dark Web Influence in Modern Web Apps - Shah, Sarthak; Anuja Phapale (MultiTech Publisher, 2023)
This paper delves into the crucial aspects of authentication and authorization in modern web applications with a focus on enhancing data security. It explores the use of Node.js, a versatile server-side language, for building web applications and discusses the significance of a secure website for establishing trust between clients and servers. The research covers the implementation of authentication using packages and hashing algorithms, emphasizing the importance of